MoS2 coated separator as an efficient barrier for inhibiting shuttle effect of polysulfide. Issue 11 (1st August 2019) - Liu, Shoufa; Zhou, Zhaofeng; Liu, Dancheng
Abstract: Functional separators have become one of the hot topics for improving the electrochemical performance of the Li-S batteries. This is mainly due to the positive effect of the functional separators for efficiently inhibiting the shuttle effect of soluble polysulfide. Based on this reason, MoS2 coated separators are prepared and used as an efficient barrier for inhibiting shuttle effect in the Li-S battery. The as-prepared MoS2 coated separators exhibit perfect wettability. Therefore, the whole battery could achieve rapid Li-ion diffusion. Besides, the metal sulfide MoS2 provides chemical adsorption for the polysulfide. As a result, comparing with the pristine separator, the Li-S battery that used MoS2 coated separator shows higher specific capacity and more excellent cycle stability.